2014
DOI: 10.1016/j.ejvs.2014.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Mural Thrombus and the Progression of Abdominal Aortic Aneurysms: A Large Population-based Prospective Cohort Study

Abstract: These findings suggest that ILT may play a part in the progression of AAAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 17 publications
1
89
1
Order By: Relevance
“…In 9 studies, AAA diameter was described as a marker for expansion8, 17, 19, 21, 40, 56, 57, 58, 59 and in 9 as a marker for rupture 34, 37, 60, 61, 62, 63, 64, 65, 66. Overall, the data are reliable because 2570 patients in total were included and 8 studies were appraised with low bias risk, 7 with medium risk, and only 3 with high risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 9 studies, AAA diameter was described as a marker for expansion8, 17, 19, 21, 40, 56, 57, 58, 59 and in 9 as a marker for rupture 34, 37, 60, 61, 62, 63, 64, 65, 66. Overall, the data are reliable because 2570 patients in total were included and 8 studies were appraised with low bias risk, 7 with medium risk, and only 3 with high risk.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the data are reliable because 2570 patients in total were included and 8 studies were appraised with low bias risk, 7 with medium risk, and only 3 with high risk. In 7 studies, significant correlations with expansion were demonstrated in 958 patients in total ( r =0.30–0.83),8, 21, 40, 56, 57, 58 and Norman et al measured faster growth in patients with a large (≥4 cm; n=112) versus small AAA (3–4 cm; n=433) 19. In 6 studies, with a total of 552 patients, significant outcomes were demonstrated for AAA diameter as a marker for rupture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As outlined in Figure 1, our search identified 20 eligible studies [3][4][5][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] reporting the association of CAD and AAA growth, which included data on a total of 7238 AAA patients. The study design and patient characteristics, detailed measurements of AAA diameters, and growth rates of AAA are summarized in Tables 1, 2, and 3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of them, we identifi ed seven eligible studies [9][10][11][12][13][14][15] reporting the association of BMI and AAA growth rates, which included data on a total of 3,768 AAA patients. The patient and AAA characteristics, the details of diameter measurement, and the association between BMI and AAA growth rates are summarized in Table 1 In a prospective study by Burillo et al [13], 122 male patients with a >30 mm AAA were scanned annually with a mean observation time of 8.1 years.…”
Section: Resultsmentioning
confidence: 99%